Characterization of carbon dots synthesized from plant-based extracts via the hydrothermal method - Wardana, Fatah Ari Kusuma; Maharani, Chlara Naren; Arbi, Aliffia Widyasari Putri; Zandi F., Mohammad Arya; Aflaha, Rizky (Greensusmater, 2025)
Cdots are carbon-based nanoparticles and luminescent materials that are safe for humans, the environment, and have many potential applications. Natural precursors using local plants can be utilized, and a green synthesis approach can be used to fabricate Cdots that are advantageous in terms of sustainability, availability, low cost, and minimal toxic waste. In this study, the hydrothermal method was chosen because the process is simple, does not require a catalyst, and is suitable for natural materials. The fabricated Cdots from various plant-based extract precursors using the hydrothermal method are investigated for the chemical and optical property changes that occur during the conversion of natural extracts into Cdots. Fourier-transform infrared (FTIR) spectra show that functional groups such as O–H and C=C remain present after the Cdots synthesis process. The UV-Vis spectra show a shift in the absorption band, indicating the formation of sp² aromatic domains and π-π* transition in the Cdots structure, compared to plant-based extracts. These results show great potential of local plants as base material for producing Cdots that can be beneficial for various applications.